1929
DOI: 10.1037/h0073302
|View full text |Cite
|
Sign up to set email alerts
|

Second report on Lady, the "mind-reading" horse.

Abstract: I N THE January number of this JOUKNAL we reported on a study of Lady, a "mind-reading" horse. This study was made at Richmond, Va. during the academic year of 1927-28. The (then three-year-old) filly had been claimed by the owner, Mrs. C. D. Fonda, to be of such superior intelligence as to be able to reply to questions by touching lettered blocks, and to execute mentally simple arithmetical problems. Of this superior intelligence we obtained no evidence; on the other hand we were able to show that Lady did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1933
1933
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In 1928, accompanied by his mentor William McDougall, Rhine was invited to attest to the paranormal abilities of Lady Wonder, a “mind reading” horse. Though initially convinced that this was an authentic case of cross-species telepathy, Rhine later concluded that Lady Wonder was actually responding to subtle unconscious physical cues (Rhine, 1929a , 1929b ). The problem of unconscious communication, the so-called “Clever Hans effect,” was particularly challenging for parapsychologists because communication was not restricted to subtle physical cues.…”
Section: Relating To the Dog As A Subjectmentioning
confidence: 99%
“…In 1928, accompanied by his mentor William McDougall, Rhine was invited to attest to the paranormal abilities of Lady Wonder, a “mind reading” horse. Though initially convinced that this was an authentic case of cross-species telepathy, Rhine later concluded that Lady Wonder was actually responding to subtle unconscious physical cues (Rhine, 1929a , 1929b ). The problem of unconscious communication, the so-called “Clever Hans effect,” was particularly challenging for parapsychologists because communication was not restricted to subtle physical cues.…”
Section: Relating To the Dog As A Subjectmentioning
confidence: 99%
“…Nothing was discovered that failed to accord with it, and no other hypothesis proposed seems tenable in view of the results." 4 Later in the same year Lady was again investigated (4) with a revision of the former view. After 500 tests the investigators were forced to conclude "that the telepathic ability we earlier found the horse to possess has been now almost if not entirely lost and that Lady has become merely a trained animal conditioned to a system of signals made up of indicative body movements, voice inflections and whip movementt."…”
mentioning
confidence: 99%